2017
DOI: 10.1021/acs.cgd.7b01366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Peculiarities of LiFePO4 Hydrothermal Synthesis Using In Situ Calvet Calorimetry

Abstract: Peculiarities of the hydrothermal synthesis of the lithium iron phosphate cathode material are studied using in situ Calvet calorimetry. Staging and temperature intervals of the phase formation process are determined as a function of the concentration of the initial reagents. Obtained results revealed a clear correlation between observed heat absorption behavior and lattice parameters, morphology, and electrochemical performance of the obtained LiFePO 4 materials. Lowering temperature of the precursor dehydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…17,18 The necessity of such studies is also preceded by the admirable electrochemical performance of olivine-type cathode materials (prepared by low-temperature methods such as hydrothermal processes) as well as by the significant amount of structural defects forming along these synthesis routes. 6,10,11,14 Lithium-rich (or lithium-excess) lithium iron phosphate (termed further as Li-rich LFP) as a novel generation of highperformance battery materials was introduced in a recent work of Park et al 17 It was shown that the presence of Li in Fe sites in Li 1+δ Fe 1−δ PO 4 (0 < δ < 0.05) decreases the first-order phase transition energy barrier, as well as Li + diffusion barriers along the [010] direction. 17,18 Besides this, the presence of Li − Fe defects energetically destabilizes the Fe + Li -related defects, thus improving Li + transport in the channels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17,18 The necessity of such studies is also preceded by the admirable electrochemical performance of olivine-type cathode materials (prepared by low-temperature methods such as hydrothermal processes) as well as by the significant amount of structural defects forming along these synthesis routes. 6,10,11,14 Lithium-rich (or lithium-excess) lithium iron phosphate (termed further as Li-rich LFP) as a novel generation of highperformance battery materials was introduced in a recent work of Park et al 17 It was shown that the presence of Li in Fe sites in Li 1+δ Fe 1−δ PO 4 (0 < δ < 0.05) decreases the first-order phase transition energy barrier, as well as Li + diffusion barriers along the [010] direction. 17,18 Besides this, the presence of Li − Fe defects energetically destabilizes the Fe + Li -related defects, thus improving Li + transport in the channels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that depending on the initial precursor concentration, the formation of this "antisite iron phosphate" and the reaction with Li + to produce the final LiFePO 4 phase can take place as two consecutive stages or as merging of these two stages into one. The observed changes in the reaction mechanism result in profound difference in the unit cell parameters of the triphylite phase, particle morphology, and electrochemical properties of the obtained LiFePO 4 samples [35].…”
Section: Na-bearing Triphylite-lithiophilite Structural Analogous and Their Derivatives As Promising Cathode Materialsmentioning
confidence: 96%
“…It was found that depending on the initial precursor concentration, the formation of this "antisite iron phosphate" and the reaction with Li + to produce the final LiFePO4 phase can take place as two consecutive stages or as merging of these two stages into one. The observed changes in the reaction mechanism result in profound difference in the unit cell parameters of the triphylite phase, particle morphology, and electrochemical properties of the obtained LiFePO4 samples [35]. According to [63], direct thermal oxidation of sarcopside, Fe3(PO4)2, above 450 °С, makes it possible to obtain heterosite, FePO4, according to the reaction Fe3(PO4)2 + ¾ O2 → 2 FePO4 + ½ Fe2O3, which leads to the extraction of iron from the sarcopside structure.…”
Section: Na-bearing Triphylite-lithiophilite Structural Analogous and Their Derivatives As Promising Cathode Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, we demonstrated that the electrochemical capacity of the hydrothermally prepared LiFePO 4 drastically depends on the initial solution concentration. 35 To detect possible structural changes accompanying this dependence, we have performed Rietveld structure refinement from powder X-ray diffraction data of the samples prepared with various solution concentrations (see Table 1). The refinement of the occupancy factors for the M1, M2 and P positions have been performed with the full occupancy of the O1, O2 and O3 positions.…”
mentioning
confidence: 99%